Invested : changing forever the way Americans invest - Schwab, Charles (Currency, 2019)
"In this deeply personal memoir, Schwab describes his passion to have Main Street participate in the growing economy as investors and owners, not only earners. Schwab opens up about his dyslexia and how he worked around and ultimately embraced it, and about the challenges he faced while starting his fledgling company in the 1970s. A year into his grand experiment in discounted stock trading, living in a small apartment in Sausalito with his wife, Helen, and new baby, he carried a six-figure debt and a pocketful of personal loans. As it turned out, customers flocked to Schwab, leaving his small team scrambling with scarce resources and no road map to manage the company's growth. He recounts the company's game-changing sale to Bank of America - and how, in the end, the merger almost doomed his organization... A remarkable story of a company succeeding by challenging norms and conventions through decades of change, Invested also offers unique insights and lifelong principles for listeners - the values that Schwab has lived and worked by that have made him one of the most successful entrepreneurs of our time."--